Study on enzyme activities and metabolomics of two Penicillium chrysogenum strains during fermentation of soybean paste - Sun, Xiaodong; Yang, Hong; Huo, Guangwei; Li, Linlin; Lyu, Guozhong (Frontiers in Microbiology, 2025)
In this study, two strains of Penicillium chrysogenum JSPP6_1 and GJY1_3 were isolated from naturally fermented soybean paste. In order to understand the potential role of the two strains in the fermentation of soybean paste, both strains were used for fermenting soybean paste, respectively. The fermentation period was 45 days, with samples taken every 5 days. Protease activities of GJY1_3 and JSPP6_1 reached their maximum value on the 15th day of fermentation, 108.95 ± 6.38 and 70.79 ± 2.13 U/mL, respectively. Lipase activities of JSPP6_1 reached the maximum at the 15th day of fermentation (14.52 ± 0.68 U/mL), while that of GJY1_3 reached the maximum at the 20th day of fermentation (7.41 ± 0.75 U/mL). Samples were taken for the metabolomic study on day 15 of fermentation. Fifty-three different metabolites were obtained, of which 33 were known, including seven amino acids, 18 organic acids and anhydrides, as well as a small amounts of sugars, glycolic acids and alcohols. Seventeen metabolic pathways were identified, of which six pathways were significant. The results showed that JSPP6_1 could produce more lipase, and the relative levels of various organic acids were higher in JSPP6_1. GJY1_3 may produce more protease, the relative contents of various amino acids being very higher in GJY1_3, including glutamic acid and glutamine, which are flavor amino acids. Both strains showed obvious functional differences in fermenting soybean paste.